7n-13=6

Simple and best practice solution for 7n-13=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7n-13=6 equation:


Simplifying
7n + -13 = 6

Reorder the terms:
-13 + 7n = 6

Solving
-13 + 7n = 6

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '13' to each side of the equation.
-13 + 13 + 7n = 6 + 13

Combine like terms: -13 + 13 = 0
0 + 7n = 6 + 13
7n = 6 + 13

Combine like terms: 6 + 13 = 19
7n = 19

Divide each side by '7'.
n = 2.714285714

Simplifying
n = 2.714285714

See similar equations:

| 7+3(4x-4)=6-5(2x+1) | | x*sqrt(x-3)=4 | | x^2+0.5x-0.01=0 | | 8=8x+8 | | 3+4(5x-6)=6-4(2x+1) | | h(x)=2x^2+x-10 | | x^2-7xy+6y^2= | | y-8=-5(x+1) | | 6=k(12) | | 2.96x-2.6=-3.47x+7.47 | | 10p-3(3p-6)=4(3p-6)-8p | | y=10-2(y-4) | | -18x^2+61xy+7y^2=0 | | 2x^2=6p-20 | | 2z=4z-8 | | 2x^2-6p=-20 | | V-7+1=14+5v | | log5(x^4y^9/6) | | 4x-101=12x-53 | | 7y=4y+9 | | 8-4x=-10+x | | f(x)=senx | | 0.25m+0.75m=2 | | 6x^2-13x+0=0 | | 4x-201=12x-53 | | 5-(-3y)=-9y+3y | | -7/9x=28 | | -4s=-12 | | X^2y-3x^2= | | -18x^2-65xa-7a^2=0 | | 43=15+0.5x | | 2cosx-sin^2x+2=0 |

Equations solver categories